Features of interrogation of minors who are victims of violence - N. E. Miloradova; N. A. Pashko (Law and Safety)
The main provisions on the organization and conduction of interrogation of minors who are victims of violence have been revealed. The concept of physical, sexual and psychological violence against a child has been studied. The features of interrogation of minors who are victims of violence and their significance in criminal proceedings have been theoretically analyzed. The author has determined the subject matter, object and tasks of interrogation of minors and features of the impact of violence on the development of a child and evidence provided by this child.